An investigation of two animal models of anxiety : central administration of corticotropin-releasing factor on the behaviour and neurochemistry of rats, and the effect of pharmacotherapy on spontaneous stereotypical behaviour and NMDA receptor function in mice - Richter, Lelanie (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScMedSc)--Stellenbosch University, 2004.